Media and culture: an introduction to mass communication - Campbell, Richard (New york: St. Martin's Press, 1998)
Contents: part 1. mass media and the cultural landscape. part 2. sounds and images. part 3. words and pictures. part 4. the business of mass media. part 5. democratic expression and the mass media.
Notes p. 471 - 478 credits p. 489 - 490 index p. 491 - 505
Keywords: Cultura Popular